The differences between uncooked meat and meat floss from two difference sources of meats (beef and carabeef) - Shahrai, Nurul Nuraliya (2016)
Meat is a source of protein, vitamins and mineral in diet but most of meats cannot be differentiated after had being processed especially red dark meat such as cattle meat (beef) and buffalo meat (carabeef). In term of price, beef was more expensive then carabeef .Visually, both type of meat could be differentiated by their fat color and this parameter was the most importance thing. There was no significant differences between value of hue but significantly difference (p<0.05) in chroma and color. Beef mostly showed chroma 3,very pale yellow but carabeef showed 1-2 chroma level. In this experiment, both meats were evaluated based on Warner-Bratzler shear force test, color, ultimate pH, chemical composition, and histological of each samples by using Scanning electron microscope (SEM). By selecting some part of meat from fresh market which were Longissimus dorsi (LD;Loin) muscle ,Gluteus Medius (GM; Rump) muscle and Semitendenous (ST;Round) muscle , the raw beef gave the pH level 5.89, higher (p<0.05) than imported beef (5.67) and carabeef (5.61). The result was almost the same which ultimate pH<6.0. The percentage of drip loss showed the range in between 11.36%-12.37% with no significantly difference (p>0.05). Percentage of cooking loss also gave the same result as percentage of drip loss (p>0.05) which in between 25.40-32.38%. The meat color of carabeef more reddish than beef and imported beef but the range was in between L*=30-L*=32.4 with slightly difference (p>0.05). The toughest meat texture (p<0.05) was indicated by carabeef with 1454.5 kgf and beef showed the lowest force (484.9 kgf) for machine needed to clamp the meat. Beef gave higher moisture content (81.45%) than carabeef (79.04%) and imported beef (79.08%). Fat content in raw meats for making meat floss was in between 0.15-0.40% with (p>0.05). Higher crude protein was showed in beef (19.56%) than imported beef (18.78%) and carabeef (18.48%).Meat floss was one of the traditional meat based-product popular among Malaysians. Three commercial meat floss were prepared by using Semitendenous m. (ST;Round) from three type of samples as collected from markets and analyzed to determine their physical characteristics, chemical composition, histological view and sensory evaluation. The results showed that pH and tenderness of meat floss were in between 5.28-5.60, 333-350 kgf, and local beef floss show the highest (p<0.05) pH level (5.56) and tenderness (345.46 kgf). All three type of meat floss showed the brightness range in between 20.57%-21.57%, (p>0.05) but the highest redness and yellow pigment percentage was imported meat floss with 9.1% and 11.11% with (p<0.05). The result moisture, fat and protein contents were within the range of 11.0-13.60%, 17.30-19.30%, 26.11-31.95%, respectively. Histological characteristic of raw meats and meat floss was evaluated by SEM and the result showed that the sarcomere length and the diameter size of muscle fiber influenced tenderness of meat. Sensory evaluation showed that panelists cannot differentiate three (3) type of the meat floss and the appearance almost the same (p>0.05). Without the panelists knowing the sample sources, panelists selected that the imported beef floss as slightly higher (p<0.05) palatability score than another. However, there was no significant difference between overall acceptability for local meat floss, imported meat floss and carabeef floss. So, as a conclusion, beef and carabeef had a lot of similarity in term of their meat floss and their raw physiochemical characteristics but their fat color was the obviously comparable.